Pembuatan Kolom Monolit Mixed-Mode untuk Pemisahan Fenol dalam Kromatografi Cair Sistem Kapiler - Aster Rahayu; Joni Aldilla Fajri; Lee Wah Lim; Toyohide Takeuchi (Universitas Ahmad Dahlan, 2018)
A Mixed-Mode monolithic column prepared from Pentaeritrytol Tetraacrylate (PETRA) and Ethylene dimathacrylate (EDMA) was investigated and used in capillary liquid chromatography. The polymer composition was optimized by varying percentage ratio of monomer and porogens. Column A with rasio 35/65 (monomer/porogen) showed the optimum ratio. The polymerization of acrylic groups were conducted by in-situ preparation in capillary fused silica. Three phenol compounds were separated using this monolithic column using acetonitrile 100% as eluent. Monolith PETRA-EDMA also could work to separate polar and non-polar compound simultaneously by HILIC mode using acetonitrile 90% as eluent. The morphology surface of monolith was observed by scanning electron microscope (SEM) and mechanical stability in term of pressure drop was observed as well.